Back Cover: Ultra‐Thin Hollow Carbon Nanospheres for Pseudocapacitive Sodium‐Ion Storage (ChemElectroChem 3/2015). Issue 3 (11th March 2015) - Yun, Young Soo; Cho, Se Youn; Kim, Haegyeom; Jin, Hyoung‐Joon; Kang, Kisuk
<x xml:space="preserve">Abstract</x> Asymmetric hybrid capacitors that use the pseudocapacitive sodium‐ion storage behaviors of ultra‐thin, hollow carbon nanospheres as a faradic electrode show remarkable electrochemical performance, as shown by H.‐J. Jin and K. Kang et al. on p. 359.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>